Scenario and Policy of Decent Nutrition and Food Security in the Post-Covid-19 in Nepal - Kabita Maharjan; Deepak Chaudhary (Borong Newinera Publisher, 2021)
The Covid-19 has drawn a new debate on the issue of food security and nutrition. The literature suggests a positive relationship between food security and nutrition. For low-income countries, access to nutritious food has been challenging. Literature reveals that Nepal faces poor food security and nutrition for decades and this issue has been more surfaced after the Covid-19. This paper explores the prospect of food security along with nutrition based on secondary data and reviews. Food security has been associated with the production, stock, access, and utilization. The utilization normally refers to the use of varieties of nutrition for the human body that is related to the immunity system. Agriculture is the prime occupation of the country as the two-third population depends on agriculture for livelihood. However, the subsistence form of agriculture has been dominated. Due to the lack of agricultural production, Nepal faces poor nutrition and faces mal-nutrition problems. Many of the districts in the western and far-western hilly regions of the country have been faced with food scarcity and malnutrition has become a common phenomenon. Moreover, Covid 19 has further highlighted the issue of food security and nutrition. As the Covid-19 is related to immunity power and its association is with nutritious food is crucial. The policy of the government has prioritized from grass root level to eliminate hunger and malnutrition though there are still challenges.